The Effect of Administering Apis dorsata Forest Honey on Liver Histopathological Changes of Rats (Rattus norvegicus) Exposed to Physical Stress - Widjiati, - (2023)
The objective of this study was to determine the effect of Apis dorsata forest honey on the liver histopathological changes of white rats (Rattus norvegicus) exposed to physical stress. This study used 24 rats which were divided into 4 groups. The positive control group (C+) was only given a stressor and distilled water orally, the treatment group 1 (T1) was given a stressor + honey 2g/rat/day, T2 was given a stressor + honey 4g/rat/day, and T3 was given a stressor + honey 6g/rat/day. All treatments were carried out within 14 days. The results showed that there was a significant difference (p<0.05) between the C+ control group (3.44a ± 0.622; 3.52a ± 0.109; 1.76a ± 0.384) and the treatment group1 /T1 (1.13b ± 0.389; 2, 48c ± 0.438; 0.84b ± 0.260) in terms of reduced level of liver damage, however, there was no significant difference (p> 0.05) between the C+ control group (3.44a ± 0.622 ; 3 .52a ± 0.109; 1.76a ± 0.384) and treatment group2 / T2 (3.72a ± 0.268; 3.64ab ± 0.260; 1.90a ± 0.400) and T3 (3.84a ± 0.167; 3.88a ± 0.178; 2 .48a ± 0.840). It can be concluded that the administration of Apis dorsata honey to rats exposed to physical stress within 14 days can reduce the level of liver damage with an effective dose of 2g/rat/day. However, excessive consumption of honey causes adverse effects on the liver as seen in the T2 and T3 treatment groups with doses of honey 4g/rat/day and 6g/rat/day which can increase the risk of liver damage. Keywords: liver damage; swimming exercise; wild honey